Analyzing the Impact of Political Instability on Myanmar's Financial Sector and Economic Growth - Soe, May Ei Ei; Panthamit, Nisit; Chaiboonsri, Chukiat (Future Science / FSH-PH Publications, 2025)
Prior to the February 1, 2021, coup, Myanmar experienced steady economic progress due to moderate political and economic reforms. However, the coup significantly disrupted this trajectory, placing the economy in a precarious state. This study examines the impact of political instability on Myanmar’s financial sector and economic growth from 2006 to 2023, with a focus on key macroeconomic factors: Political Stability, Inflation, and Unemployment. Using the Markov Switching Dynamic Regression (MSDR) model, the analysis captures how these variables influence economic growth under different economic regimes. The findings reveal that Political Stability and Inflation positively contribute to economic expansion, while Unemployment has a negative effect. The MSDR model uniquely identifies two distinct economic regimes: recessionary periods, where the effects of these variables are weaker or insignificant, and periods of economic boom, where all factors significantly drive growth. These results highlight the critical role of maintaining political stability, controlling inflation, and reducing unemployment to foster sustainable development. The study provides actionable policy recommendations for Myanmar and offers insights for neighboring economies and international policymakers on managing political and economic crises. Strengthening stability, promoting inclusive growth, and enhancing financial resilience are essential steps toward long-term economic progress